An exploration of the protective effect of rodent species richness on the geographical expansion of Lassa fever in West Africa. - Kyung-Duk Min; Jusun Hwang; Maria Cristina Schneider; Yeonghwa So; Ju-Yeun Lee; Sung-Il Cho (Public Library of Science (PLoS), 2021)
Background Lassa fever (LF) is one of the most devastating rodent-borne diseases in West Africa, causing thousands of deaths annually. The geographical expansion of LF is also a concern; cases were recently identified in Ghana and Benin. Previous ecological studies have suggested that high natural-host biodiversity reduces the likelihood of spillover transmission of rodent-borne diseases, by suppressing the activities of reservoir species. However, the association of biodiversity with the geographical expansion of LF has not been the subject of epidemiological studies. Methodology/principal findings We conducted a spatial analysis based on sociodemographic, geographical, and ecological data, and found that higher rodent species richness was significantly associated with a lower risk of LF emergence in West Africa from 2008 to 2017 (Odds Ratio = 0.852, 95% Credible Interval = 0.745-0.971). Conclusions/significance The results reinforce the importance of the 'One Health' approach by demonstrating that a high level of biodiversity could benefit human health.